Animal Research on Campus: Reflections on My Experience in the Field. Issue 6 (2nd November 2018) - Dolby, Nadine
Abstract : In this essay, I discuss my experience as a member of my university's Institutional Animal Care and Use Committee (IACUC). Using Blum's (2016 ) model of experiential learning (or "learning in the wild"), I reflect on the connected processes of reading, thinking, seeing, hearing, smelling, talking, and listening that were the basis for my education about the use of animals for research on university campuses. In conclusion, I suggest that faculty members, staff members, and students have an obligation to understand, and work to change, the lives of the animals who exist among us.